On Validity of Christianiy in postsecular times - Cobo Cucurull, Josep (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The Christian religion will not survive the crisis of Christendom. Nor did Roman religion survive the fall of the Empire. For no religion, as a cultural phenomenon, can overcome the sociohistorical conditions that made it possible. However, the catholicity of the Christian kerygma —whether it remains relevant after the decline of the Christian religion— does not depend on the rebirth of Christianity, which is otherwise unfeasible, but on the fact that the God who revealed himself to us on Golgotha is not comparable to what is religiously understood as divine. Modern criticism of religion was, in fact, earlier Christian, to the point that Christianity is closer to atheism than to religion. The Incarnation —the fact that God is still no one without the body with which he identifies— transcends epochs and cultures. And it transcends them because its horizon is not the world, but that of its end.